New approaches of the Next-gen collaborative design platform - Vlachodimos Georgios (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The architecture design process always changes because the software always updates with new tools and the development - innovation is in the first line of progress. The human-machine cooperation has become commonplace through Computer-Aided Design tools, but a more improved collaboration appears possible only through an endeavor into a kind of artificial design intelligence and Augmented Reality. According to all the above, the research shown in this paper the core ideas - identifying design specifications - of a next-generation collaborative design platform. The direct coupling of introducing multi-industry systems - tools, 3D databases, AEC, and Open-BIM technologies opens up totally new ways of approaching architectural design problems resulting in a new flexible modeling workflow with real-time visualization. Finally, this critical examination research makes an original contribution to changing 'attitude' towards the 3d modeling of architectural design thinking. A collaborative design platform creating a more efficient and versatile architecture.